Residency, Identity, and Language Attitude in Food-Talk - Sastika Seli (STKIP PGRI Lubuklinggau, 2018)
The research aims at describing the influence of residency between urban and suburban language speakers in showing language attitude when talking about food. The data were collected through participant observation as well as recording technique, noting technique and ethnographic interview. The findings show the identity of urban and suburb language speakers in talking about food including 1) urban identity description of health dealing with diet and disease, 2) suburban identity description of the concept of villagers who love traditional food, and 3) suburban identity description of traditional food ritual. Language attitude in food-talk between urban and suburban language speakers including 1) attitude indicated by the use of pronoun we; 2) the descipription of special food vocabularies refer tofood process and menus; and 3) attitude indicated in lexical borrowing. The distinc attitude and identity between urban and suburban language speakers are determined by the description of special food vocabularies related to process, material and menus. Suburban people are proud of explaining their food ritual in gathering food ingredient and processing it using their mother tongue. In urban society, speakers tend to talk about food dealing with modern life style, such as health.